(untitled) (Bangladesh Journal of Child Health, 2014)
Acute post-streptococcal glomerulonephritis (APSGN) is characterized by abrupt onset of hematuria, edema, hypertension, oliguria and impaired renal function following streptococcal group A â hemolytic streptococcal throat and skin infection. There is a declining incidence of APSGN worldwide, particularly in industrialized nations because of easier and earlier access to competent medical treatment of streptococcal infections and the widespread use of fluorination of water since virulence factors in streptococcus pyogens are reduced with fluoride exposure. But in the underdeveloped world, global burden of APSGN continues to be significant with lower estimate of 9.3 to 9.8 cases per 1,00,000 population per year to higher estimates as high as three times these values. Furthermore, clusters of cases are more frequently reported in poor communities in industrialized countries while epidemics of more than 100 cases are reported in the middle ranger countries with mean annual health expenditure per capita of about 550 US dollars. APSGN typically follows 1to2 weeks after pharyngeal infection and 2 to 4 weeks after skin infection by nephritogenic strains of group A â hemolytic streptococcus in a range of 5 15 years of age. Subclinical cases are 4 10 times higher than symptomatic patients. The acute phase generally resolves within 4-8 weeks but microscopic hematuria may persist for 1-2 yr after the initial presentation. Acute complications of symptomatic patients are hypertensive heart failure, encephalopathy and retinopathy. There can be acute renal failure and rarely rapidly progressive ( crescentic) glomerulonephritis, hyperkalemia, hyperphosphatemia, hypocalcemia and acidosis. Treatment is directed towards reduction of hypertension, but prompt address of complications are essential to avoid immediate mortality. Heart failure is treated with diuretic and anti-hypertensive, digoxin is ineffective. Hypertensive encephalopathy is treated by I.V phenobarbitone for convulsion, supportive measures for unconsciousness and blood pressure control. Acute renal failure is managed by supportive measures, rarely requires dialysis. Short and long term prognosis is excellent, with1% mortality during acute stage and 1% ending up with chronic kidney disease, but in higher age group abnormal urinalysis are present in higher number of patients. DOI: http://dx.doi.org/10.3329/bjch.v38i1.20025 Bangladesh J Child Health 2014; VOL 38 (1) : 32-39